2013
DOI: 10.1073/pnas.1312348110
|View full text |Cite
|
Sign up to set email alerts
|

T-box transcription factor T-bet, a key player in a unique type of B-cell activation essential for effective viral clearance

Abstract: IgG2a is known to be the most efficient antibody isotype for viral clearance. Here, we demonstrate a unique pathway of B-cell activation, leading to IgG2a production, and involving synergistic stimulation via B-cell antigen receptors, toll-like receptor 7 (TLR7), and IFNγ receptors on B cells. This synergistic stimulation leads to induction of T-box transcription factor T-bet expression in B cells, which, in turn, drives expression of CD11b and CD11c on B cells. Tbet/CD11b/CD11c positive B cells appear during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
317
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(349 citation statements)
references
References 55 publications
28
317
1
Order By: Relevance
“…Interestingly, inclusion of a TLR9 ligand in the antigen resulted in substantially decreased IL-4 mRNA and increased IFN-γ mRNA (Fig. S3B), which is consistent with the observed increase in isotype switching to IgG2a b (32,33). Thus, differential modulation of cytokine and costimulatory pathways of T FH cells likely established distinct selection pressures in the GC reactions occurring in the presence or absence of a TLR9 ligand.…”
Section: Tlr9supporting
confidence: 75%
See 1 more Smart Citation
“…Interestingly, inclusion of a TLR9 ligand in the antigen resulted in substantially decreased IL-4 mRNA and increased IFN-γ mRNA (Fig. S3B), which is consistent with the observed increase in isotype switching to IgG2a b (32,33). Thus, differential modulation of cytokine and costimulatory pathways of T FH cells likely established distinct selection pressures in the GC reactions occurring in the presence or absence of a TLR9 ligand.…”
Section: Tlr9supporting
confidence: 75%
“…In contrast, the class switch to IgG2a was similar in both Myd88 −/− and Myd88 +/+ B cells in mixed bone marrow chimeras, whereas it was defective if all B cells were Myd88 −/− . Therefore, we hypothesize that Myd88 +/+ B cells in the GC of mixed bone marrow chimeric mice were able to promote the ability of T FH cells to induce B cells of either genotype to class switch to IgG2a, for example, by production of IFN-γ (32,33,68). Alternatively, prior studies have demonstrated that in some immunizations, the class switch to IgG2a can be a B cell-intrinsic function of TLR9 signaling (6,69).…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that aged female mice accumulate ABCs (49, 121-123), a subset of B cells defined by the expression of cell surface CD11c and the transcription factor T-bet (49,123,124). We have also reported that ABCs accumulate in several different mouse models of SLE (MRL lpr , NZB/NZW, MER -/-) and coincide with the appearance of autoantibodies (49, 50).…”
Section: Sex-dependent Changes In the Aging Immune Systemmentioning
confidence: 86%
“…We have identified TLR7, IFNGR, and B cell antigen receptor signaling as necessary and sufficient for the upregulation of T-bet expression in B cells (123,124), which eventually causes B cells to assume the ABC phenotype. We have confirmed that TLR7 is most efficient in driving this process when compared with other TLRs (124).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…9 Other immune cells such as natural killer, dendritic, B, and CD8-positive-T cells also express T bet. [10][11][12][13][14] The T-bet has a pleiotropic role, directs the expression of interleukin 1α, macrophage inflammatory protein-1α in dendritic cells, 15 interferon γ in Th1 cells, 16 and class switching in B cells. 17 A recent study revealed that intraglomerular T-bet expression is associated with antibody-mediated rejection in Chinese people.…”
Section: T-bet-positive Mononuclear Cell Infiltration Is Associated Wmentioning
confidence: 99%